PERAN BADAN PENGAWAS PEMILU (BAWASLU) DALAM PENANGANAN PELANGGARAN PILKADA TAHUN 2020 DI KOTA MAKASSAR - Hainidar, Hainidar; Mappamiring, Mappamiring; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aims to determine the role of the Election Supervisory Agency (BAWASLU) in Handling Violations in the 2020 elections in Makassar City.  The type of research used is a qualitative research method with a descriptive type of research.  Data collection techniques using observation, interviews, and documentation.  The results showed that 1) Handling of violations of the code of ethics for election organizers based on data there were three violations, then related to its implementation in the Covid-19 pandemic situation, it was also found that health protocol violations had been handled according to existing procedures, 2) handling of election administration violations based on data  there is one violation that was found in one of the city of Makassar and has been forwarded to the District PPK for follow-up according to its level, 3) the handling of election crime violations based on the data there are 36 violations, related to the handling there are 5 violations stop at this first discussion because there are no  proven then 30 violations stopped in this second discussion because they did not have enough evidence and there was 1 violation stopped in the third discussion because the suspect and several witnesses ran away because they were constrained at the time until they were SP 3 status Keywords: Role, Bawaslu, Handling Violations, Local Elections